PERHITUNGAN PREMI KOMODITAS PADI BERBASIS INDEKS CURAH HUJAN DENGAN DISTRIBUSI WEIBULL DAN DISTRIBUSI EKSPONENSIAL CAMPURAN - I KADEK WIDIADNYANA; KOMANG DHARMAWAN; NI KETUT TARI TASTRAWATI (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2026)
Agricultural insurance is insurance that exists in the agricultural sector. Agricultural insurance is relatively recently introduced in Indonesia, there are three types of agricultural insurance, agricultural insurance based on losses, price-based agricultural insurance, and index-based agricultural insurance. In this study, the type of agricultural insurance used is index-based insurance, especially based on the rainfall index. The purpose of this study was to determine the procedures required to determine the price of agricultural insurance premiums based on the rainfall index and calculate agricultural insurance premiums using the Weibull distribution or mixed exponential distribution. Furthermore, where the premium price is relatively smaller and close to the insurance premium recommended by the government. In this study, the premium price generated is different for the two distributions, with a not too large difference in the range of rainfall resulting from the simulation of rainfall obtained by using a mixed exponential distribution to get a smaller premium value.